Differences In Interpretation Between The District KPU And BAWASLU Of Gorontalo District Related To Administrative Violations Of The 2020 Regional Elections In Gorontalo District - Nuna, Moh. Maskun; Moonti, Roy Marthen; Kadir, Yusrianto; Bunga, Marten; Kasim, Muslim (International Journal of Law and Society, 2024)
The purpose of the research is to find out the causes of differences in interpretation between the Gorontalo Regency KPU and Bawaslu Gorontalo Regency regarding administrative violations of the 2020 elections in Gorontalo Regency and how the process of resolving administrative violations of the 2020 elections in Gorontalo Regency by the Gorontalo Regency KPU and Bawaslu Gorontalo Regency. This research uses two legal research methods, namely: Normative and empirical legal research to find answers to the differences in interpretation between the KPU and Bawaslu Gorontalo Regency regarding administrative violations of the 2020 Pilkada in Gorontalo Regency. The difference in interpretation between the Regency KPU and Bawaslu Gorontalo Regency regarding administrative violations is caused by overlapping statutory provisions. Where in Law Number 10 Year 201 concerning Pilkada, the two institutions are given the authority to examine and decide administrative violations, then the two institutions in deciding administrative violations have their own guidelines where Bawaslu is guided by Perbawaslu while the KPU itself is guided by KPU Regulations. This certainly does not provide legal certainty for justice seekers in election administration violations and the process of resolving administrative violations in the 2020 Pilkada in Gorontalo Regency, namely through DKPP and Constitutional Court decisions. We do not have to face different decisions between the two institutions because DKPP is an ethical judicial institution while the Constitutional Court is a legal judicial institution. Although there has been a decision from the Constitutional Court, it does not change the DKPP's decision because until now there has been no ethics court to appeal the DKPP's decision.